Analysis Business Intelligence Systems in the Outsourcing Industry Using Soft System Methodology - Satriya Nugroho, Chrismantya Dwi; Siti Astuti, Endang; Darmawan, Ari (FIA UB, 2024)
This study aims to determine the problem of implementing business intelligence in the outsourcing industry with complex IOIS integration. The data sources come from the Tcompany business processes (internal) and the business processes from partner companies (external) to obtain relevant information for the business Intelligence system. Soft System Methodology is used for system analysis and modeling to integrate technology (complex) and human (soft) systems. Using the view of soft systems thinking and rooted in the paradigm of situational complexity, the capacity of all-around real-world systems that are messy and unstructured by looking at the success factors of implementing business intelligence system managerially through organizational, process, and technology aspects. The final result expected by the researcher is in the form of suggestions for improvements that the company can make with a systematic approach and corporate culture. Implementing business intelligence in the outsourcing industry faces issues due to conflicts of interest between business and technology. CEOs focus more on growth and profits, while CIOs are more concerned with technological infrastructure and operational efficiency. Addressing this challenge requires initiating conversations between CEOs and CIOs and a comprehensive assessment of both business and technology strategies to ensure enhanced alignment.